Digital transformation of Malaysian small and medium enterprises - Tajudeen, Farzana Parveen; Moghavvemi, Sedigheh; Thirumoorthi, Thinaranjeney; Phoong, Seuk Wai; Bahri, Elya Nabila Binti Abdul (Emerald points., 2025)
Digital transformation entails utilizing emerging technology to enhance operational effectiveness, generate novel offerings, and expand consumer reach, including both local and global markets. It enables small and medium-sized enterprises (SMEs) to compete effectively, adjust to evolving market conditions, and prosper in the digital era, but there are unique characteristics to SMEs that raise challenges in this transformation. Digital Transformation of Malaysian Small and Medium Enterprises explores the factors influencing digital transformation in Malaysian SMEs, focusing on both internal and external aspects. Chapters delve into organizational, technological, and environmental factors that play a crucial role in SMEs' digital journey. By understanding these drivers, policymakers, government bodies, and industries can accelerate the adoption of digital technologies, directly impacting SME growth and relevance in the evolving marketplace. Digital Transformation of Malaysian Small and Medium Enterprises is an invaluable resource for scholars, practitioners, policymakers, and everyone involved in SMEs' digital transformation path. It provides a thorough overview of the concepts, challenges, and opportunities surrounding this essential activity in Malaysia.